Quantitative fluorescence imaging determines the absolute number of locked nucleic acid oligonucleotides needed for suppression of target gene expression. Issue 2 (20th November 2018) - Buntz, Annette; Killian, Tobias; Schmid, Daniela; Seul, Heike; Brinkmann, Ulrich; Ravn, Jacob; Lindholm, Marie; Knoetgen, Hendrik; Haucke, Volker; Mundigl, Olaf
Abstract: Locked nucleic acid based antisense oligonucleotides (LNA-ASOs) can reach their intracellular RNA targets without delivery modules. Functional cellular uptake involves vesicular accumulation followed by translocation to the cytosol and nucleus. However, it is yet unknown how many LNA-ASO molecules need to be delivered to achieve target knock down. Here we show by quantitative fluorescence imaging combined with LNA-ASO microinjection into the cytosol or unassisted uptake that ∼10 5 molecules produce >50% knock down of their targets, indicating that a substantial amount of LNA-ASO escapes from endosomes. Microinjected LNA-ASOs redistributed within minutes from the cytosol to the nucleus and remained bound to nuclear components. Together with the fact that RNA levels for a given target are several orders of magnitude lower than the amounts of LNA-ASO, our data indicate that only a minor fraction is available for RNase H1 mediated reduction of target RNA. When non-specific binding sites were blocked by co-administration of non-related LNA-ASOs, the amount of target LNA-ASO required was reduced by an order of magnitude. Therefore, dynamic processes within the nucleus appear to influence the distribution and activity of LNA-ASOs and may represent important parameters for improving their efficacy and potency.